Gustav Gloom and the Four Terrors - Castro, Adam-Troy (Castro, Adam-Troy. Gustav Gloom, 2013)
When Gustav convinces Fernie's safety-conscious father to enter the Gloom Mansion with Fernie and Perlie to help rescue Gustav's father from the Dark Country, there is a prison break from the Hall of Shadow Criminals, endangering them all.